Penggunaan Aplikasi Wordwall Untuk Meningkatkan Kemampuan Mengenal Huruf Abjad Pada Anak Usia Dini (Penelitian Tindakan Kelas di Kelompok A RA Ar-Raudhah Ujungberung Kota Bandung) - Fauziah, Trisma Nurul; Rosyidah, Ida; Muftie, Zaenal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Based on a preliminary study conducted by researchers in group A RA Ar-Raudhah Jl. Neglasari I No. 10 with seven students, the background is the ability to recognize letters of the alphabet in early childhood that has not developed. This problem arises because the media provided by the teacher is not varied enough in introducing letters of the alphabet to children. This study aims to determine: (1) The ability to recognize letters of the alphabet in Group A RA Ar-Raudhah before using the wordwall application (2) How to use the wordwall application to improve the ability to recognize letters of the alphabet in Group A RA Ar-Raudhah in each cycle, and (3) How the ability to recognize letters of the alphabet in Group A RA Ar-Raudhah after using the wordwall application throughout the cycle. The method used in this study is quantitative and qualitative research, also known as a mixed approach. A mixed approach involves collecting quantitative and qualitative data, combining the two forms of data, and using different designs, incorporating philosophical assumptions and theoretical frameworks. The research subjects were seven children from Group A of RA Ar-Raudhah. Data collection techniques used included observation, performance, and documentation. Based on the calculation of the results of pre-cycle observations, the ability to recognize letters of the alphabet in early childhood gets an average of 50 with the criteria of not yet developed. The process of using the wordwall application can be seen from the teacher's activities in cycle I obtained an average of 84% with a very good category, and cycle II obtained an average of 93% with a very good category. While the child's activities in cycle I obtained an average value of 57% with a less category, and cycle II obtained an average value of 64% with a sufficient category. The results of the calculation of the performance sheet regarding the ability to recognize letters of the alphabet in children of group A RA Ar-Raudhah in cycle I the first and second actions got an average value of 69 with a sufficient category, for cycle II the first and second actions got an average value of 85 with a very good category.